HUBUNGAN KINERJA PENYULUH PERTANIAN DENGAN KEPUASAN DAN KEPENTINGAN PETANI - Tambunan, Herlina Yolanda; Deras, Stefanus; Berasa, Resda Isni (Jurnal Agriust, 2026)
This research aims to describe the relationship between agricultural extension worker performance and farmer satisfaction and interests. The study population included managers and members of farmer groups. Sampling for farmer group managers was random, while sampling for members was purposive. The research data were purely primary data from respondents through structured interview guidelines. Data were analyzed descriptively statistics. The results of the study indicate that the performance dimensions of agricultural extension workers, including "tangibility, reliability, responsiveness, certainty, and empathy," are generally perceived by farmers as important. The tangibility and responsiveness aspects are given the highest priority. Farmer satisfaction levels range from moderately satisfied to satisfied. The tangibility, responsiveness, and empathy dimensions are in the satisfied category, while the reliability and certainty dimensions are still in the moderately satisfied category. The performance of extension workers is still needed, especially in the reliability and certainty aspects.